Mitochondrial reactive oxygen species control T cell activation by regulating IL-2 and IL-4 expression: mechanism of ciprofloxacin-mediated immunosuppression - Kamiński, Marcin; Sauer, Sven; Klemke, Claus-Detlev; Süss, Dorothee; Okun, Jürgen G.; Krammer, Peter H.; Gülow, Karsten (The journal of immunology, 2010)
This article shows that T cell activation-induced expression of the cytokines IL-2 and -4 is determined by an oxidative signal originating from mitochondrial respiratory complex I. We also report that ciprofloxacin, a fluoroquinolone antibiotic, exerts immunosuppressive effects on human T cells suppressing this novel mechanism. Sustained treatment of preactivated primary human T cells with ciprofloxacin results in a dose-dependent inhibition of TCR-induced generation of reactive oxygen species (ROS) and IL-2 and -4 expression. This is accompanied by the loss of mitochondrial DNA and a resulting decrease in activity of the complex I. Consequently, using a complex I inhibitor or small interfering RNA-mediated downregulation of the complex I chaperone NDUFAF1, we demonstrate that TCR-triggered ROS generation by complex I is indispensable for activation-induced IL-2 and -4 expression and secretion in resting and preactivated human T cells. This oxidative signal (H2O2) synergizes with Ca2+ influx for IL-2/IL-4 expression and facilitates induction of the transcription factors NF-κB and AP-1. Moreover, using T cells isolated from patients with atopic dermatitis, we show that inhibition of complex I-mediated ROS generation blocks disease-associated spontaneous hyperexpression and TCR-induced expression of IL-4. Prolonged ciprofloxacin treatment of T cells from patients with atopic dermatitis also blocks activation-induced expression and secretion of IL-4. Thus, our work shows that the activation phenotype of T cells is controlled by a mitochondrial complex I-originated oxidative signal.